Dynamics and Control of Energy Harvesting from a Non-ideally Excited Portal Frame System with Fractional Damping - Tusset, Angelo M.; Rocha, Rodrigo T.; Iliuk, Itamar; Balthazar, Jose M. [UNESP]; Litak, Grzegorz (Springer Nature, 2021)
This paper analyzes the dynamics of a nonlinear piezoelectric energy harvesting device connected to a portal frame accounting for the influence of the fractional order derivative introduced due to damping. The identification of the behavior of the portal frame is obtained by the analysis of time histories, phase planes, FFT spectrum and 0-1 test. The numerical analyses show that the fractional order sustains the chaotic behaviors of the system. The average harvested power is computed for each value of the chosen fractional derivative, to demonstrate that the system response considerably affects the harvested power. To suppress the chaotic behavior a control technique is proposed associated with two controls: the feedback control by SDRE control and the feedforward control.
Keywords: Chaos; Energy harvesting; Fractional-Order; Piezoelectric devices; SDRE control